Quasifission Dynamics in Microscopic Theories - Godbey, Kyle; Umar, A. S. (Frontiers in Physics, 2020)
In the search for superheavy elements quasifission reactions represent one of the reaction pathways that curtail the formation of an evaporation residue. In addition to its importance in these searches quasifission is also an interesting dynamic process that could assist our understanding of many-body dynamical shell effects and energy dissipation thus forming a gateway between deep-inelastic reactions and fission. This manuscript gives a summary of recent progress in microscopic calculations of quasifission employing time-dependent Hartree-Fock (TDHF) theory and its extensions.